2020
DOI: 10.1681/asn.2020010052
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling of AKI in a Murine Model Reveals Novel Transcriptional Signatures, Profibrotic Phenotype, and Epithelial-to-Stromal Crosstalk

Abstract: BackgroundCurrent management of AKI, a potentially fatal disorder that can also initiate or exacerbate CKD, is merely supportive. Therefore, deeper understanding of the molecular pathways perturbed in AKI is needed to identify targets with potential to lead to improved treatment.MethodsWe performed single-cell RNA sequencing (scRNA-seq) with the clinically relevant unilateral ischemia-reperfusion murine model of AKI at days 1, 2, 4, 7, 11, and 14 after AKI onset. Using real-time quantitative PCR, immunofluores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 120 publications
15
127
0
Order By: Relevance
“…Consistent with the results obtained in the in silico analysis, the expression of PPP‐related genes – G6pdx , Taldo1 , Tkt , and Prps1 – was significantly increased in ischaemic mice, compared with sham mice (Figure 6E–H). It is important to note that elevated expression of PPP‐related genes was also observed during the repair phase in a publicly available single cell RNA dataset [29] (supplementary material, Figure S7E–H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results obtained in the in silico analysis, the expression of PPP‐related genes – G6pdx , Taldo1 , Tkt , and Prps1 – was significantly increased in ischaemic mice, compared with sham mice (Figure 6E–H). It is important to note that elevated expression of PPP‐related genes was also observed during the repair phase in a publicly available single cell RNA dataset [29] (supplementary material, Figure S7E–H).…”
Section: Resultsmentioning
confidence: 99%
“…Our data imply that during the reperfusion phase, the cell strategically chooses the PPP over glycolysis. Once metabolic functions have been restored, it does not seem advantageous for the cell to shuttle glucose through a pathway that does not yield ATP; however, our analysis of a single cell RNA dataset [29] showed that increased expression of several PPP‐related genes is maintained for up to 7 days following IRI in the proximal tubular cell population. This further suggests that the activation of the PPP may be responsible for the generation of ‘chemical supplies’ needed for cellular repair.…”
Section: Discussionmentioning
confidence: 99%
“…The fast development of single-cell RNA sequencing (scRNA-seq) technology allows the inquiry of transcriptomic profiles and signaling pathways in diverse cell types from a given sample simultaneously, and unlike bulk RNA-seq, it can define comprehensive gene sets at the single-cell level (9,10). Recently, this new methodology has been employed in various renal diseases (11)(12)(13)(14). In the present study, we applied scRNAseq to kidney samples from patients with IgAN to identify gene expression at the single cell level, and explore novel cellular interactions and crucial molecular pathways contributing to the disease development.…”
Section: Introductionmentioning
confidence: 99%
“…This novel technology has been used successfully in several organs—for example, to study Prominin 1+ liver progenitors [ 114 ], Dach1–downregulated lymphoid progenitors [ 115 ] and KTR5+ lung progenitors in COVID-19 patients [ 116 ]. Within the past few years, an increasing number of research groups have applied this strategy to define the cell populations of the kidneys in mice and humans [ 117 , 118 , 119 , 120 ]. In a very recent study, Rudman-Melnick et al identified the transcriptional signature of all cell populations in an experimental model of AKI, highlighting the presence of previously undescribed injury-related molecules [ 119 ].…”
Section: Outlook On the Future Of Renal Progenitorsmentioning
confidence: 99%
“…Within the past few years, an increasing number of research groups have applied this strategy to define the cell populations of the kidneys in mice and humans [ 117 , 118 , 119 , 120 ]. In a very recent study, Rudman-Melnick et al identified the transcriptional signature of all cell populations in an experimental model of AKI, highlighting the presence of previously undescribed injury-related molecules [ 119 ]. Such an approach could potentially reveal novel mechanisms activated in renal progenitors following AKI, leading to the identification of potential molecular targets.…”
Section: Outlook On the Future Of Renal Progenitorsmentioning
confidence: 99%